Cross-field Diffusion Effects on Particle Transport in a Solar Coronal Flux Rope - Edin Husidic; Nicolas Wijsen; Luis Linan; Michaela Brchnelova; Rami Vainio; Stefaan Poedts (The Astrophysical Journal Letters)
Solar energetic particles associated with solar flares and coronal mass ejections (CMEs) are key agents of space weather phenomena, posing severe threats to spacecraft and astronauts. Recent observations by Parker Solar Probe indicate that the magnetic flux ropes of a CME can trap energetic particles and act as barriers, preventing other particles from crossing. In this Letter, we introduce the novel COCONUT+PARADISE model to investigate the confinement of energetic particles within a flux rope and the effects of cross-field diffusion (CFD) on particle transport in the solar corona, particularly in the presence of a CME. Using the global magnetohydrodynamic coronal model COolfluid COroNal UnsTructured (COCONUT), we generate background configurations containing a CME modeled as a Titov–Démoulin flux rope (TDFR). We then utilize the particle transport code PArticle Radiation Asset Directed at Interplanetary Space Exploration (PARADISE) to inject monoenergetic 100 keV protons inside one of the TDFR legs near its footpoint and evolve the particles through the COCONUT backgrounds. To study CFD, we employ two different approaches regarding the perpendicular proton mean free path (MFP): a constant MFP and a Larmor radius-dependent MFP. We contrast these results with those obtained without CFD. While particles remain fully trapped within the TDFR without CFD, we find that even relatively small perpendicular MFP values allow particles on the outer layers to escape. In contrast, the initially interior trapped particles stay largely confined. Finally, we highlight how our model and this Letter's results are relevant for future research on particle acceleration and transport in an extended domain encompassing both the corona and inner heliosphere.